EVALUATION OF COASTLINE DEVELOPMENT OVER PERIODS IN CUA VIET AREA BY APPLICATION OF REMOTE SENSING TECHNIQUE AND GEOGRAPHIC INFORMATION SYSTEM (GIS) - Cham, Dao Dinh; Son, Nguyen Thai (Vietnam Journal of Marine Science and Technology, 2016)
The development of the coastline in Cua Viet outlet area from 1952 to 2015 was quantitatively evaluated using remote sensing technique and geographic information system (GIS). The result of the research shows that in the Cua Viet outlet area the accretion and erosion phenomena occur in a very complex manner, with erosion predominating over accretion in both scale and intensity, in which the coast sections with the largest scale and highest intensity of erosion are usually located near the outlet (both inside and outside the outlet). In the coast section inside the outlet, the erosion on the northern side occurs more intensively than on the southern side, with the erosion rate reaching -1.51 to -2.24 m/year, whereas the accretion rate is 1.15 to 1.70 m/year. The ratio between the erosional and accretional rates is 1.0 to 1.5 times. In the coast section outside the outlet, erosion occurs much more intensively, with its rate from - 2.74 to - 8.18 m/year, whereas the accretion rate is only 0.12 to 2.41 m/year. The ratio between the erosion and accretion is 1.0 to 38 times. Recently, the newly-built Cua Viet seawall has partially reduced the process of coastal erosion, the beach starts to consolidate in the foot area.